Lei antiterrorismo brasileira (nº 13.260/2016): atentado contra o sistema penal acusatório? - Fonseca, Nedson Danildo da (Universidade Federal Rural do Semi-Árido, 2017)
The challenge of facing the strengthening of terrorist organizations has led many States to develop special legislation at their domestic level, although in many cases, they have been criticized for hurting procedural guarantees of the rule of law. Thus, the purpose of the present study was to analyze whether the possibility of judicial action provided for in the aforementioned Law, especially by allowing to the judge the ex officio decree of precautionary measures in the policial inquest phase, is consistent with the accusatory criminal system. Therefore, the focus was centered on the investigation of specialized literature and the jurisprudence of the Federal Supreme Court. It was first observed how the discussions on terrorism have developed in the ambit of international organizations, as well as the Brazilian participation in the conventions that deal with the matter. Next, the characteristics of the accusatory criminal system were discussed, without losing sight of the need for fundamental guarantees in the light of the Federal Constitution of 1988. Finally, we sought to analyze how Law n.13.260/2016 violates the accusatory system in line with the jurisprudential understanding developed by the Federal Supreme Court. It is concluded that the aforementioned normative legislation, by providing for the possibility of ex officio judicial proceedings in the investigative and procedural phase, violates the separation between the organs that integrate the procedural triad (accuser, defense and adjudicator), the management and the initiative of the tests, which should be left to the interested parties in their demarcation. The mechanism creates a kind of court of law never observed in Brazilian law, since the investigation activity is the responsibility of the judicial police, directly or with the assistance of the competent organ to offer the denunciation.
Artigo Acadêmico
Keywords: Terrorismo. .; Sistema Penal Acusatório; Garantismo Processual Constitucional; Lei Antiterrorismo; Terrorism; Accusatory Criminal System; Constitutional Procedural Garantism; Antiterrorism law; CIENCIAS SOCIAIS APLICADAS::DIREITO